Conscientização ambiental no ensino fundamental I - SOUZA, Maria Nilde Luz de (Instituto Federal do Amapá, 2022)
This work aims to demonstrate the pertinent needs in relation to environmental awareness in elementary school I, and as the implementation of environmental education in schools is being developed, the tools for investigating the information used were bibliographic searches, searching through scientific articles and in the works of various actors, understandings of the debatable topic. In the course of evolution, humanity has been constantly changing its standard of living, increasingly making it an exploratory society of natural resources, building a more consumerist and capitalist society, and with this scenario it brings environmental problems and all the consequences for a quality of life, in order to minimize impacts and prevent possible environmental catastrophes, bodies and programs with policies aimed at protecting and inspecting the environment arose, AE is a program with educational and transformative actions, and together schools promote social awareness attitudes , in order to have citizens more aware of ecological issues, schools have the role of providing access to knowledge through their actions, directing the responsibility for environmental awareness and sustainability, in elementary education, environmental education has been of a preventive nature, making it possible from an early age tracing values and building knowledge, so that students can develop more critical attitudes of an ecological perception.